Implementasi E-Commerce Berbasis Laravel untuk UMKM Lissiger dengan Desain Mobile-Responsive - Bagas Tri Panji Susilo; Fitria Fitria (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The rapid advancement of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt electronic commerce in order to improve their business competitiveness. Lissiger MSME, located in Bandar Lampung and engaged in the production of traditional Lampung siger crowns, still relies on conventional marketing and manual transaction recording, resulting in limited market reach and inefficient administrative processes. This study aims to design and develop a mobile-responsive ecommerce platform to expand digital marketing reach and automate transaction management for Lissiger MSME. The system was developed using the Agile Scrum methodology through three structured sprint cycles. Laravel framework, Bootstrap 5, and MySQL were utilized to develop the application System evaluation was conducted using Black Box Testing to verify system functionality and User Acceptance Testing (UAT) involving 10 respondents, consisting of one MSME owner and nine prospective customers, to evaluate user acceptance.The developed platform provides a 50% Down Payment (DP) transaction mechanism and an interactive visualization feature presenting nine stages of siger production as a cultural educational medium. The Black Bo Testing results showed a 100% success rate across 11 functional test scenarios, while the UAT achieved an average score of 88.70%, indicating that the system is highly acceptable for users. These findings demonstrate that the proposed platform effectively supports digital marketing expansion and transaction management for Lissiger MSME. The main contribution of this study is the development of a mobile-responsive e-commerce platform that integrates a 50% Down Payment (DP) payment mechanism aligned with MSME business processes and an interactive visualization of siger production as a medium for cultural education and preservation within a single system.